Contemporary cinema of Africa and the diaspora - Prabhu, Anjali (Chichester, West Sussex, UK Wiley Blackwell, 2014)
"Focuses on art house cinema and discusses commercial African cinema"--Provided by publisher.
Machine generated contents note: Chapter 1 Introduction; Contemporary Cinema of Africa and the Diaspora: Parameters and Contexts PART I: SPACE Chapter 2 Walking in the City: Education of the Spectator in Harrikrisna Anenden's La Cathedrale Chapter 3 Framing the City: Africanizing Viewer and Viewed through Angle, Distance, Genre, and Movement PART II: CHARACTER Chapter 4 Models of African Femininity Chapter 5 African Masculinity: "We Don't Need Another Hero" / Relentless Return of the Allegory Chapter 6 Revolutionary Personhood: Revolutionize the Spectator, or Stop, Thief! PART III: NARRATIVE Chapter 7 Documentary Film: Situating a Style Chapter 8 African Narration: Narration of Africa Chapter 9 Jean-Marie Teno: Creating an African Repertoire Chapter 10 Conclusion: Inside/Outside or How to Make a Film About Africa Today Glossary Works Cited Index .
Includes bibliographical references (pages 238-245) and index.
Keywords: Motion pictures -- Africa -- History and criticism; Experimental films -- Africa -- History and criticism; Motion picture industry -- Africa; African diaspora